The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4149/av_2013_02_130
|View full text |Cite
|
Sign up to set email alerts
|

The broad spectrum of hantaviruses and their hosts in Central Europe

Abstract: Summary. -Hantaviruses are considered to be emerging viruses due to their increasing significance as human pathogens and their cyclic reappearance during outbreaks. Central Europe is an important endemic region for hantavirus infections. Reflecting the presence of all relevant small mammals serving as reservoir hosts, close to all recognized European hantaviruses occur also in Central Europe. Important human pathogens, Puumala and Dobrava-Belgrade viruses, are present and cause hemorrhagic fever with renal syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 51 publications
0
27
0
2
Order By: Relevance
“…While outbreaks of HFRS have long been known to occur in central Europe (Klempa et al, 2013), including Germany (Hofmann et al, 2008; Krüger et al, 2001), the Czech Republic (Pejcoch et al, 2010) and Slovakia (Sibold et al, 1999b), reports of hantavirus infection and disease in Poland have been conspicuously uncommon, despite the existence of the same reservoir rodent species. Previously, TULV was isolated from the common vole in central Poland (Song et al, 2004), and anti-hantavirus antibodies were reported among Polish mammalogists (Sadkowska-Todys et al, 2007) and forestry workers (Grygorczuk et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While outbreaks of HFRS have long been known to occur in central Europe (Klempa et al, 2013), including Germany (Hofmann et al, 2008; Krüger et al, 2001), the Czech Republic (Pejcoch et al, 2010) and Slovakia (Sibold et al, 1999b), reports of hantavirus infection and disease in Poland have been conspicuously uncommon, despite the existence of the same reservoir rodent species. Previously, TULV was isolated from the common vole in central Poland (Song et al, 2004), and anti-hantavirus antibodies were reported among Polish mammalogists (Sadkowska-Todys et al, 2007) and forestry workers (Grygorczuk et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies have indicated that SWSV is widespread throughout Europe and Asia across the vast distribution of its soricid reservoir, in Austria, Czech Republic, Finland, Germany, Hungary, Russia, Slovakia and Slovenia (Kang et al, 2009a; Klempa et al, 2013; Korva et al, 2013; Resman et al, 2013; Schlegel et al, 2012b). SWSV has also been detected in the Siberian large-toothed shrew ( S. daphaenodon ) and tundra shrew ( S. tundrensis ) in Russia (Yashina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This fact, in addition to the recent discovery of A. flavicollis infected with the strain DOBV or DOBVAf in southeastern Europe (the Balkan region), suggests that further phylogenetic discussions on DOBV and SAAV are required [97]. Therefore, the ICTV approved SAAV and DOBV as viral species, and more recently, the hantaviruses DOBV and SAAV have been suggested to be subdivided into four related genotypes:Dobrava, Sochi, Kurkino and Saaremaa [146]. …”
Section: Hantavirus Hostsmentioning
confidence: 99%
“…Hantaviral diseases have recently acquired increasing importance because of expanded spectrum of natural reservoir hosts [11][12][13][14][15]. Since there are no drugs against HTVs, vaccination remains the most desirable option for disease prevention.…”
Section: Introductionmentioning
confidence: 99%